Cardiac and Metabolic Physiology of Early Larval Zebrafish (Danio rerio) Reflects Parental Swimming Stamina - Burggren, Warren W.; Gore, Matthew (Frontiers in Physiology, 2012)
Swimming stamina in adult fish is heritable, it is unknown if inherited traits that support enhanced swimming stamina in offspring appear only in juveniles and/or adults, or if these traits actually appear earlier in the morphologically quite different larvae. To answer this question, mature adult zebrafish (Danio rerio) were subjected to a swimming performance test that allowed separation into low swimming stamina or high swimming stamina groups. Adults were then bred within their own performance groups. Larval offspring from each of the two groups, designated high (LHSD) and low stamina-derived larvae (LLSD), were then reared at 27°C in aerated water (21% O2). Routine (fH,r) and active (fH,a) heart rate, and routine (M.O2,r) and active (M.O2,a) mass-specific oxygen consumption were recorded from 5 days post fertilization (dpf) through 21 dpf, and gross cost of transport and factorial aerobic metabolic scope were derived from M.O2 measurements. Heart rate generally ranged between 150 and 225 b•min-1 in both LHSD and LLSD populations. However, significant (P<0.05) differences existed between the LLSD and LHSD populations at 5 and 14 dpf in fH,r and at days 10 and 15 dpf in fH,a. M.O2,r was 0.04 to 0.32 μmol•mg-1•hr-1, while M.O2,a was 0.2 to 1.2 μmol•mg-1•hr-1. Significant (P<0.05) differences between the LLSD and LHSD populations in M.O2,r occurred at 7, 10 and 21 dpf and in M.O2,a at 7 dpf. Gross cost of transport was 6-10 µmol O2 . µg-1 . m-1 at 5 dpf, peaking at 14-19 µmol O2 . µg-1 . m-1 at 7-10 dpf, before falling again to 5-6 µmol O2 . µg-1 . m-1 at 21 dpf, with gross cost of transport significantly higher in the LLSD population at 7 dpf. Collectively, these data indicate that inherited physiological differences contributing to enhanced stamina in adult parents appear in their larval offspring well before attainment of juvenile or adult features.